The use of biogenic Fe3+ and H2SO4 generated from pyrite waste to enhance bornite bioleaching: A potential utilization of acid mine drainage. (December 2022) - Hong, Maoxin; Wang, Wei; Li, Laishun; Liu, Yang; Tong, Lizhi; Qiu, Guanzhou; Yang, Baojun; Wang, Jun
Graphical abstract: Highlights: A two-stage method combing pyrite and bornite bioleaching processes was proposed. Biogenic Fe 3+ and H2 SO4 from pyrite significantly enhanced bornite bioleaching. Actual acid mine drainage could also improve bornite bioleaching. The results can provide a guide for potential utilization of AMD. Abstract: The huge amount of pyrite wastes not only occupy a lot of lands, but its oxidation also releases considerable amounts of ferric iron and acid into the environment to form acid mine drainage (AMD). On the other hand, ferric iron and acid are ideal leaching agents for copper sulfides such as bornite (Cu5 FeS4 ). In this study, the influence of biogenic Fe 3+ and H2 SO4 generated from pyrite bioleaching on the extraction of copper from bornite was investigated using a two-stage method combining the two bioleaching processes (first pyrite oxidation, then bornite leaching). In the pyrite oxidation process, pyrite bioleaching leachate (PBL) with varying pH and iron concentrations was collected at different times for subsequent bornite bioleaching. The result showed that the bioleaching of bornite was significantly improved in PBL, and the copper extraction of bornite was increased by almost 75 % after bioleaching in PBL with pH of 1.25 and total iron concentration (TFe) of 4 g/L. The results of XRD, SEM and XPS proved that the increase of solution pH during bornite bioleaching would cause the precipitation of iron to form jarosite or schwertmannite on the surface of bornite. Besides, natural acid mine drainage could also improve bornite bioleaching to a certain extent. The finding can provide an important guide for the bioleaching of low-grade copper sulfides as well as the potential utilization of AMD.